SARS-CoV-2 Humoral and Cellular Immune Responses of Patients With HIV After Vaccination With BNT162b2 mRNA COVID-19 Vaccine in the Tel-Aviv Medical Center. (23rd February 2022) - Tau, Luba; Turner, Dan; Adler, Amos; Marom, Rotem; Ahsanov, Svetlana; Matus, Natasha; Levi, Inbar; Gerber, Gal; Lev, Shir; Ziv-Baran, Tomer; Hagin, David; Freund, Tal; et al.
Abstract: Background: Little is known about vaccine efficacy and sustainability among people with HIV (PWH). We estimated humoral and cellular immune responses postvaccination with BNT162b2 mRNA coronavirus disease 2019 (COVID-19) vaccine among PWH in Tel-Aviv Medical Center. Methods: The vaccine humoral response was evaluated by measuring immunoglobulin G (IgG) titers of antispike receptor-binding domain antibodies (anti-RBD IgG). Cellular response was assessed by stimulating donor peripheral blood mononuclear cells with pooled complete S-peptide mix. Results: One hundred thirty-six PWH who completed 2 doses of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine were tested for anti-RBD IgG and compared with 61 vaccinated health care workers (HCWs). The antibody titers were similar between the groups (median, 118 BAU/mL for PWH and 101.4 BAU/mL for HCWs; P = .231), although the mean time from second vaccine was 4.5 months in PWH and 6.7 months in HCWs ( P < .0001). Longer time from second vaccine dose was associated with decreased antibody level, as were CD4 counts <300 cells/µL compared with higher CD4 counts (25.1 BAU/mL vs 119.3 BAU/mL, respectively; P = .047). There was no difference in cellular immune response between vaccinated PWH, convalescent unvaccinated PWH, and vaccinated HCWs. Conclusions: The humoral immune response of PWH was comparable to that of HCWs after BNT162b2 mRNA vaccination. Cellular immune response did not differ between vaccinated PWH, convalescent PWH, and vaccinated HCWs. PWH with CD4 counts <300 cells/µL (n = 9) had lower antibody titers compared with patients with counts >300 cells/µL (n = 127).